The use of adaptive arrays for the prediction of human behavior - Tanhehco, Benito Li (1971)
This thesis describes the use of adaptive arrays as a means of pattern recognition. The adaptive array is a group of weighing factors which weigh the various input characteristics of some given patterns. Decision as to which pattern the given set of input belongs depends on this weighing scheme. The weighing factors are obtained by a training process which requires the availability of sample cases for each given pattern. Once the factors are obtained, they can be used on other cases not belonging to the sample group but which are classified under the various patterns trained. The more distinguishing the characteristics are of the given patterns, the faster it is to obtain the adaptive array and the more accurate the decisions from the adaptive array is when applied on test cases. This thesis above show the derivation of adaptive arrays for two types of application. One is for judging an engineering student's final course performance given his entrance examinantion performance. The other is for judging whether a male or female person is considered psychologically normal pr abnormal based on his response to a set of questions.